Dhimmi and the assumption of leadership of Muslim countries: a comparative study with the Palestinian Law - Muhammad Husni, Ahmad; Keleibi, Yusuf 'Atiyyah; Omar, Anwar Fakhri; Niteh, Muhammad Yosef (Scholars Middle East Publishers, 2018)
This study examines the extent of eligibility of dhimmi to assume the leadership of an Islamic country. The problem of the study lies in removing the requirement of Islam in the head of a Muslim country; and the extent of the eligibility of members of non-Muslim minorities to hold this office. I wanted from this study to explain the Shariah view and look into authorities of each opinion; and additionally, the position of the Palestinian law for a non-Muslim to lead a Muslim country. The aim of looking at these authorities and discussing them is to reach to the Islamic view which is in line with the Shariah provisions, and to explain the extent upon which the Palestinian law has granted religious minorities this right. The study adopts inductive approach in getting the opinions and authorities; and the study then follows the analytical approach in analyzing these views and authorities and came out with comfortable strong evidence. I started by explaining the nature of Islamic political system and that it is discretionary branch of Shariah. The study further addressed views on the ruling of leadership of dhimmi in Islamic countries, which ranged between two views: The first view and the holders are the vast majority of scholars and thinkers; they say it is prohibited. And the second opinion which is the view of some contemporary thinkers and scholars where they say dhimmi is allowed to lead Muslims. And after studying both views and their authorities the study preferred the prohibition of leadership of non-Muslim on Muslims, and this is based on the principle of justice and there is no violation of values, principles and foundations of citizenship. Finally, the Palestinian Basic Law does not require specific religion for the presidential candidate of the state.